The relationship between personality factors and dyadic satisfaction - Călin, Mariana Floricica; Sandu, Mihaela Luminița; Miu, Anca Sabina (Technium Social Sciences Journal, 2021)
The couple represents the basic unit of life perpetuation. The couple is generally defined as a couple or reunion of two people based on constant bonding or due to a momentary closeness. In both cases, however, the union must function, even if this is often difficult. Couple satisfaction is defined as the individual emotional state of being satisfied with the interactions, experiences and expectations within the couple's life. Couple satisfaction is an individual emotional state of being satisfied with the interactions, experiences and expectations within the couple's life. depending on the personality of the partners, they manage to relate better and thus to be more satisfied in the couple.